Psychological variables underlying political orientations in an old and a new democracy: A comparative study between Sweden and Latvia. Issue 5 (2nd August 2016) - Dimdins, Girts; Sandgren, Maria; Montgomery, Henry
Abstract : This study examines in detail the psychological variables underlying ideological political orientation, and structure and contents of this orientation, in Sweden and Latvia. Individual political orientation is conceptualized on two dimensions: acceptance vs. rejection of social change and acceptance vs. rejection of inequality. Swedish (N = 320) and Latvian (N = 264) participants completed measures of political orientation, Social Dominance Orientation (SDO), Right Wing Authoritarianism (RWA), self vs. other orientation, tolerance for ambiguity, humanism and normativism, core political values, system justification, as well as moral foundations questionnaire and portrait values questionnaire. The results showed that the relation among the measured variables was similar in both samples. Swedish participants showed stronger endorsement of egalitarian attitudes and social values, whereas we found more self‐enhancing and socially conservative values and attitudes among the Latvian participants.